2017
DOI: 10.1108/jfmm-10-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

Development of an identity model for sector brands

Abstract: Purpose The purpose of this paper is to propose an identity model for sector brands and examines its applicability for the Brasil Fashion System brand. Design/methodology/approach A systematic review of the literature on corporate brand identity models is undertaken. The interviews were carried out with two interest groups: the associations comprising the brand, and the consultancy company responsible for sector brand advisory. Findings The sector brand identity model is applicable to the Brasil Fashion Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(78 citation statements)
references
References 19 publications
(52 reference statements)
0
71
0
7
Order By: Relevance
“…Several countries have already developed this type of brand for internationalisation of their sectors (Aichner, 2014). In Brazil, the Brazilian Agency for the Promotion of exports and investments (Apex-Brasil) is responsible for developing and managing sectorial brands (Lourenção and Giraldi, 2017). This type of brand is created by Apex-Brasil in conjunction with the associations representing the sectors and it should be used at international events.…”
Section: Brand Identity and Imagementioning
confidence: 99%
See 3 more Smart Citations
“…Several countries have already developed this type of brand for internationalisation of their sectors (Aichner, 2014). In Brazil, the Brazilian Agency for the Promotion of exports and investments (Apex-Brasil) is responsible for developing and managing sectorial brands (Lourenção and Giraldi, 2017). This type of brand is created by Apex-Brasil in conjunction with the associations representing the sectors and it should be used at international events.…”
Section: Brand Identity and Imagementioning
confidence: 99%
“…A few studies have indicated a difficulty in developing the identity of sectorial brands that is suitable for all partners (Lourenção and Giraldi, 2017;Tregear and Gorton, 2009). Iversen and Hem (2008) suggest that, in order to mitigate this challenge, it is necessary, before developing the brand, to identify common attributes that participants wish to communicate and that will be represented by the shared brand.…”
Section: Analysis Of Brazilian Fashion Sectorial Brand Identity Intromentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in practical terms, understanding the personality of Brazilians may contribute to several managerial areas. The study of their personality may contribute, for example, to manage negotiations between national and international companies (Pedroso, Massukado-Nakatani, & Mussi, 2009); to understand actions related to Brazilian organizational culture (Chu & Wood, 2008); to boost exports of domestic products (Lourenção & Giraldi, 2017); and also to drive investments (Papadopoulos, Hamzaoui-Essoussi, & Banna, 2016),…”
Section: Introductionmentioning
confidence: 99%